Relationship Between Transthoracic Echocardiography and Transesophageal Echocardiography in the Anatomic and Hemodynamic Assessment of Secundum Atrial Septal Defects in Children and Adults - Rehman, Mujeeb Ur; Sathio, Shahnawaz; Chand, Raam; Shaikh, Abdul Sattar; Ahsan, Aliya Kemal; Rehman, Fazal ur; Patel, Najma (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the relationship between transthoracic and transesophageal echocardiography in the anatomic and hemodynamic assessment of secundum atrial septal defects in children and adults. Study Design: Cross-sectional study. Place and Duration of Study: Department of Paediatric Cardiology, National Institute of Cardiovascular Diseases, Karachi Pakistan, from Jul 2020 to Jun 2021. Methodology: Seventy-seven patients above three years of age with secundum atrial septal defects were included. Linear regression was used to determine any statistically significant difference between transthoracic and transesophageal echocardiography approaches. Results: Of 77 patients, there were 37(48.1%) male and 40(51.9%) female. No significant difference was noted in terms of any of the clinical parameters during transthoracic echocardiography and transesophageal echocardiography. As per transthoracic echocardiography, 35(45.5%) were noted to be deviceable, while in transesophageal echocardiography, 36(46.8%) patients were found to be deviceable (p=0.872). No emergency exploration or deaths occurred. Linear regression showed no statistically significant difference between transthoracic echocardiogram and transesophageal echocardiography findings in terms of atrial septal defects size (p=0.226), total septal length (p=0.930), RV systolic pressure (p=0.440), RV functions and TAPSE (0.748) except LV ejection fraction function findings (p<0.001). Conclusion: Anatomic and hemodynamic assessment of secundum atrial septal defects in children and adults correlated well with transthoracic and transesophageal echocardiography.